Cerebrospinal Fluid Hypernatremia Elevates Sympathetic Nerve Activity and Blood Pressure via the Rostral Ventrolateral Medulla. Issue 6 (December 2015) - Stocker, Sean D.; Lang, Susan M.; Simmonds, Sarah S.; Wenner, Megan M.; Farquhar, William B.
Abstract : Elevated NaCl concentrations of the cerebrospinal fluid increase sympathetic nerve activity (SNA) in salt-sensitive hypertension. Neurons of the rostral ventrolateral medulla (RVLM) play a pivotal role in the regulation of SNA and receive mono- or polysynaptic inputs from several hypothalamic structures responsive to hypernatremia. Therefore, the present study investigated the contribution of RVLM neurons to the SNA and pressor response to cerebrospinal fluid hypernatremia. Lateral ventricle infusion of 0.15 mol/L, 0.6 mol/L, and 1.0 mol/L NaCl (5 µL/10 minutes) produced concentration-dependent increases in lumbar SNA, adrenal SNA, and arterial blood pressure, despite no change in splanchnic SNA and a decrease in renal SNA. Ganglionic blockade with chlorisondamine or acute lesion of the lamina terminalis blocked or significantly attenuated these responses, respectively. RVLM microinjection of the gamma-aminobutyric acid (GABAA ) agonist muscimol abolished the sympathoexcitatory response to intracerebroventricular infusion of 1 mol/L NaCl. Furthermore, blockade of ionotropic glutamate, but not angiotensin II type 1, receptors significantly attenuated the increase in lumbar SNA, adrenal SNA, and arterial blood pressure. Finally, single-unit recordings of spinally projecting RVLM neurons revealed 3 distinct populations based on discharge responses to intracerebroventricular infusion of 1 mol/L NaCl: type I excited (46%; 11/24), type II inhibited (37%; 9/24), and type III no change (17%; 4/24). All neurons with slow conduction velocities were type I cells. Collectively, these findings suggest that acute increases in cerebrospinal fluid NaCl concentrations selectively activate a discrete population of RVLM neurons through glutamate receptor activation to increase SNA and arterial blood pressure. Abstract : Supplemental Digital Content is available in the text.